PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS HOTS PADA MATA PELAJARAN EKONOMI - Octavia Herliana; Riza Yonisa Kurniawan (STKIP PGRI Tulungagung, 2021)
The development of higher level thinking skills in students is needed to improve the quality of education in this 21st century. This study aims to determine the process of assessment instruments, the quality of the assessment instruments, and to determine the students high- level thinking skills which are known from the results of working on HOTS-based assessment instruments on economic subjects. The subjects in this study were the 11th Grade at SMA Negeri 1 Sooko, totaling 141 students. This type of research uses research and development methods and uses a model adopted from Sugiyono where there are 7 out of 10 steps used, including finding Potentials and Problems, collecting information, designing products, validating designs, revising designs, testing products, and revising products. The results of the item validity test resulted in 19 valid items and 1 invalid item as evidenced by looking at r count r table. R table of 134 respondents and 20 questions totaled 0.1427. The reliability test shows that the total average score of 0.425 is in the